Hubungan Praktek Manajemen dengan Ketidakhadiran Petugas Puskesmas di Kabupaten Wakatobi Tahun 2018 - Candra, Candra (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2019)
As the most important point of contact for health services, the presence of health workers at the Puskesmas must be a serious concern. If it is not managed and controlled, absenteeism can spread like a pandemic and will create various disciplinary problems for the organization. This study aims to measure the relationship between the management practices of the Puskesmas and abseteeism of Puskesmas officers in Wakatobi Regency.This study use quantitative methods with cross-sectional survey method. Samples were health worker in the Puskesmas 141 people. Data analysis using Stata 12 software. This study shows that Puskesmas management practices seen from work attitudes influence the absence of Puskesmas officers where Puskesmas officers who have poor work attitudes are more often absent, job satisfaction affects the absence of Puskesmas officers where dissatisfied Puskesmas officers have more absenteeism high. Supervision has an effect on the absence of Puskesmas officers where Puskesmas officers who get poor supervision have a higher absence rateThe absence of Puskesmas officers in the Wakatobi Regency area is still very high. The high absenteeism of this relates to poor health center management practices.